Constitutive Expression of a Dominant-Negative TGF-β Type II Receptor in the Posterior Left Atrium Leads to Beneficial Remodeling of Atrial Fibrillation Substrate. Issue 1 (24th June 2016) - Kunamalla, Aaron; Ng, Jason; Parini, Vamsi; Yoo, Shin; McGee, Kate A.; Tomson, Todd T.; Gordon, David; Thorp, Edward B.; Lomasney, Jon; Zhang, Qiang; Shah, Sanjiv; Browne, Suzanne; et al.
Abstract : Rationale: : Fibrosis is an important structural contributor to formation of atrial fibrillation (AF) substrate in heart failure. Transforming growth factor-β (TGF-β) signaling is thought to be intricately involved in creation of atrial fibrosis. Objective: : We hypothesized that gene-based expression of dominant-negative type II TGF-β receptor (TGF-β-RII-DN) in the posterior left atrium in a canine heart failure model will sufficiently attenuate fibrosis-induced changes in atrial conduction and restitution to decrease AF. Because AF electrograms are thought to reflect AF substrate, we further hypothesized that TGF-β-RII-DN would lead to increased fractionation and decreased organization of AF electrograms. Methods and Results: : Twenty-one dogs underwent injection+electroporation in the posterior left atrium of plasmid expressing a dominant-negative TGF-β type II receptor (pUBc-TGFβ-DN-RII; n=9) or control vector (pUBc- LacZ ; n=12), followed by 3 to 4 weeks of right ventricular tachypacing (240 bpm). Compared with controls, dogs treated with pUBC-TGFβ-DN-RII demonstrated an attenuated increase in conduction inhomogeneity, flattening of restitution slope and decreased duration of induced AF, with AF electrograms being more fractionated and less organized in pUBc-TGFβ-DN-RII versus pUBc- LacZ dogs. Tissue analysis revealed a significant decrease in replacement/interstitial fibrosis, p-SMAD2/3 and p-ERK1/2. Conclusions: : Targeted gene-based reduction of TGF-β signaling in the posterior left atrium—with resulting decrease in replacement fibrosis—led to beneficial remodeling of both conduction and restitution characteristics of the posterior left atrium, translating into a decrease in AF and increased complexity of AF electrograms. In addition to providing mechanistic insights, this data may have important diagnostic and therapeutic implications for AF. Abstract : Supplemental Digital Content is available in the text.